2018
DOI: 10.1159/000488579
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Follicular Thyroid Neoplasm with Papillary-Like Nuclear Features: Can Cytology Face the Challenge of Diagnosis in the Light of the New Classification?

Abstract: Objectives: To assess the cytological findings of noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTP), conventional papillary thyroid carcinomas (C-PTC), and invasive follicular variants of papillary thyroid carcinomas (IFV-PTC) to determine if there are cytological differences between groups. Study Design: We have reviewed all thyroid fine-needle aspiration cytology samples diagnosed between 2000 and 2017. We have included all NIFTP cases (n = 6) and randomly selected cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, studies suggest that ultrasonography is insufficient for differentiating NIFTP from invasive EFVPTC (80,81,83). Both tumours show a similar appearance in cytological examinations as well (58,76,80,83,84). This is not surprising given that NIFTP can be differentiated from invasive EFVPTC by the exclusion of capsular and vascular invasion based on histological examination of the entire tumour along with the capsule (4,35).…”
Section: Attempts At Preoperative Identification Of Niftpmentioning
confidence: 99%
“…However, studies suggest that ultrasonography is insufficient for differentiating NIFTP from invasive EFVPTC (80,81,83). Both tumours show a similar appearance in cytological examinations as well (58,76,80,83,84). This is not surprising given that NIFTP can be differentiated from invasive EFVPTC by the exclusion of capsular and vascular invasion based on histological examination of the entire tumour along with the capsule (4,35).…”
Section: Attempts At Preoperative Identification Of Niftpmentioning
confidence: 99%
“…After NIFTP was introduced as a new entity, many studies on the cytology of NIFTP have been published. Several studies on cytological diagnostic features showed that features related to NIFTP differ mainly from PTC cytopathology and to lesser extent from FVPTC cytopathology [ 67 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Niftp: Cytopathology and Summary Of Cytological Studiesmentioning
confidence: 99%
“…On the other hand, microfollicles were more frequent in NIFTP than in PTC. On nuclear level, chromatin clearing, contour irregularities, enlargement, grooves, and pseudoinclusions were statistically significantly more expressed in PTC cases than in NIFTP cases [ 67 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Niftp: Cytopathology and Summary Of Cytological Studiesmentioning
confidence: 99%
“…The identification of a potential NIFTP after a cytology review will help plan for discussions with the patient and support a more conservative surgery. Various studies have looked into the Bethesda categories where NIFTP has eventually been diagnosed to identify differences in cytological classification [8,10,12,13,19,20,21,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. In the studies conducted in the US that have utilized contemporary NIFTP criteria, more than 80% of the diagnoses fall under the AUS, SFN and SUS categories [12,19,20,21,30,31,33].…”
Section: Impact Of Non-invasive Follicular Thyroid Neoplasm With Pmentioning
confidence: 99%
“…The identification of the differences in cytology between NIFTP and I-FVPTC remains challenging. While a single study found more nuclear folds in I-FVPTC [29], others have found no distinguishing features in cytology [29,39]. Larger studies are needed in this area but given the significant overlap with its invasive counterpart, the accurate determination of NIFTP in cytology may be difficult to impossible in general practice.…”
Section: Cytomorphology Of Non-invasive Follicular Thyroid Neoplasmentioning
confidence: 99%